2013
DOI: 10.1007/s11657-013-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

Examining the impact of reimbursement on referral to bone density testing for older adults: 8 years of data from the Barwon Statistical Division, Australia

Abstract: DXA referral ratios were 1:1.6 (men) and 1:1.8 (women) for 2007-2010 vs. 2003-2006; proportions of referrals doubled for men and tripled for women from 2003 to 2010. Overall, rates of DXA utilization remained low. Policy changes may have had minimal influence on referral; thus, ongoing evaluation over time is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 24 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…Standardised fracture rates have increased by 12% in men and 8% in women between 2006 and 2012. The previously-reported increase in the uptake of BMD scanning described by Brennan et al [6] in the same geographical region appears to have had little impact on reducing fracture incidence in this time frame.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Standardised fracture rates have increased by 12% in men and 8% in women between 2006 and 2012. The previously-reported increase in the uptake of BMD scanning described by Brennan et al [6] in the same geographical region appears to have had little impact on reducing fracture incidence in this time frame.…”
Section: Discussionmentioning
confidence: 55%
“…Although previous studies have demonstrated increases in BMD scanning amongst those aged 70 years and over, it is the consensus amongst authors that scanning rates remain low [6,12]. Qualitative research from the same region as the current study reported that general practitioners (GPs) considered osteoporosis to be of low salience [13], rendering bone health as potentially less likely to be investigated than other health conditions.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Dual energy x-ray absorptiometry (DXA) is used to measure BMD, and acts as one of the key strategies to inform decision-making processes regarding low BMD and anti-fracture therapies (9,10). We recently reported there was minimal increase in the utilization of DXA by Australian men and women aged 70 years and older, after changes to national health policy introduced by Medicare Australia in 2007 (11). We found that although the proportion of men undergoing DXA doubled from 2003 to 2010, the proportion tripled for women; importantly, the overall utilization of DXA in this age group remained low (11).…”
Section: Introductionmentioning
confidence: 71%